INCREASING THE EFFICIENCY OF MANAGEMENT OF THE PERFORMANCE OF MARKETING ACTIVITIES OF THE ENTERPRISE IN THE CONDITIONS OF DIGITALIZATION AND THE POST-WAR PERIOD - LARKA, Ludmila (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article defines the main directions of digitization of the management of the effectiveness of marketing activities of the enterprise. The purpose of the article is to justify proposals for improving the digitalization of the document flow system of marketing business processes due to its design in terms of the main directions of the company’s marketing activities, to determine the role of digital marketing tools in managing the effectiveness of marketing activities. The components of document flow systems of marketing business processes have been studied. It is shown that digitalization contributes to increasing the effectiveness of marketing research and justification of marketing decisions. It was determined that the combined use of traditional and digital marketing tools allows for a synergistic effect in managing the effectiveness of marketing activities. The expediency of designing a document flow system of marketing business processes in terms of the main directions of the enterprise’s marketing activity (development of product, price, sales, communication policies, marketing management), as well as points of interaction of the functional subsystem of marketing management with the functional subsystems of production, personnel, finance and innovation management is shown. It is shown that the digitalization of marketing performance management is an integral part of the company’s digitalization strategy. It was determined that the classification of companies depending on the level of innovative activity is more appropriate for the study of innovative marketing strategies of Ukrainian enterprises. It was determined that in the post-war period, the main threats to the enterprise are the destruction of logistics chains, the shortage of own funds of enterprises and the difficulty of obtaining credit funds, the complication of business conditions due to state policy, and a high degree of uncertainty in the business environment. In such conditions, the tools of digital technologies make it possible to increase the effectiveness of managing the effectiveness of marketing activities and more rationally distribute the limited marketing budget.